COMMUNITY AWARENESS NOT TO ACTIVATE IN THE RED ZONE OF MT. SINABUNG ERUPTION - Muhammad Fahmi Siregar; Arief Wahyudi; Sri Hadiningrum; Fazli Rachman; Reh Bungana Beru Perangin-angin; Prayetno Prayetno; Majda El Muhtaj; Yusna Melianti (Jurnal Ilmiah Teunuleh, 2021)
This study aims to photograph public awareness not to move in the red zone of the eruption of Mount Sinabung. Although the government has relocated victims of the eruption of Mount Sinabung and forbade people to carry out activities in the red zone of Mount Sinabung until now there are still many people who are active in the red zone area. The research is empirical legal research. The location of this research was in Gamber Village, Subdistrict of Simpang Empat, Karo Regency. Data that was collected will be analyzed by technique qualitative analysis. The people of Gamber village carry out activities in the red zone of Mount Sinabung consciously due to several factors. first, economic factor; second, the factor of agricultural land; and third, the belief factor. In addition to the three main factors, the government's inability to persuade its people persuasively not to carry out activities in the red zone also contributes to the violation of red zone policies. Looking at the various factors mentioned above, there are inefficient ways that can encourage people to maintain what is in effect.